2005
DOI: 10.1097/01.aids.0000180095.12276.ac
|View full text |Cite
|
Sign up to set email alerts
|

HIV drug resistance acquired through superinfection

Abstract: HIV drug resistance acquired through superinfection significantly lowers the likelihood of successful antiretroviral therapy and undermines the clinical value of a patient's prior drug resistance testing and lack of prior antiretroviral use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 15 publications
0
78
0
1
Order By: Relevance
“…In theory, a more prolonged time of HIV infection could allow multiple rounds of transmission of different drug-resistant viruses, resulting in more extensive resistance patterns in drug-naive subjects tested at later stages of infection. However, findings pertaining to the relatively rare occurrence of HIV superinfection (9,25) do not seem to support this hypothesis. Multiple parallel testing of plasma and PBMCs at different time points could elucidate the kinetics of transmitted resistance over time.…”
Section: Discussionmentioning
confidence: 92%
“…In theory, a more prolonged time of HIV infection could allow multiple rounds of transmission of different drug-resistant viruses, resulting in more extensive resistance patterns in drug-naive subjects tested at later stages of infection. However, findings pertaining to the relatively rare occurrence of HIV superinfection (9,25) do not seem to support this hypothesis. Multiple parallel testing of plasma and PBMCs at different time points could elucidate the kinetics of transmitted resistance over time.…”
Section: Discussionmentioning
confidence: 92%
“…The first documented cases of HIV superinfection were found in individuals with various modes of transmission and included inter-and intrasubtype cases (1,9,17). Subsequently, multiple studies have documented superinfection in small populations of high-risk individuals (2,3,7,8,11,13,17,20,22,23,26,29). The rate of HIV superinfection in these high-risk groups was relatively frequent and was comparable to the incidence rate in similar populations from the same regions, especially if multiple viral genes were examined (3,13,14,21,24).…”
mentioning
confidence: 99%
“…There is accruing evidence for HIV-1 intra-and intersubtype superinfection in settings of intravenous drug use, structured treatment interruptions, and with strains that are resistant to antiretroviral drugs (2,4,6,22,26,28,32,39,42,43,52,60,66). Epidemiologic studies have suggested that the frequency of superinfection ranges from rare to as high as 5% per year in high-risk populations (9,10,15,20,24,27,31,40,41,51,59,65,67).…”
mentioning
confidence: 99%